Hubungan Karakteristik Pasien Dengan Perbaikan Kondisi Pasien Stroke di RSU DR. Moewardi Surakarta - Abdurrahim, Ahmad, Umi Budi Rahayu, S.Fis., M.Kes (2016)
Background: Stroke is the second leading cause of death and a major cause of disability worldwide. Stroke patients have different characteristics from one another. These characteristics can be seen on the age, sex, occupation, type of stroke, the cause of stroke, and history of stroke. Fast or slow the healing process of patients with stroke depends on the handlers provided to patients. By looking at the characteristics of the patient's medical staff can determine appropriate interventions for patients. With the improvement of conditions so the process will be run in accordance with what is expected. Objective: To determine the relationship characteristic of patients with improvement of the condition of stroke patients Methods: The study was a retrospective observational analytic approach. By using secondary data such as medical records of patients hospitalized in september until november by the number of 321 patients. Data were obtained and tested relationships using Spearman rho correlation test with 5% confidence. Results: There was a relationship of employment characteristics of the patient visits, type of stroke, and history of stroke by improving the condition of the patient. Judging from the results of the statistical test using Spearman rho correlation test showed significant values <0.05. Conclusions: No association between patient characteristics by improving the condition of stroke patients in RSU DR Moewardi Surakarta